ISLAMIC EDUCATION THOUGHTS - Herlina Herlina (IAI Al-Mawaddah Warrahmah Kolaka, 2022)
This paper will review the Biography of Hasan Langgulung, his works, the concept of Islamic education thought according to Hasan Langgulung and the relevance of Hasan Langgulung Islamic Education Thought to Current Education. Therefore, this idea can be a reference for improving education in Indonesia, especially Islamic education and become a reference for teachers in doing better learning